Etiology, Treatment and Prevention of Kidney Cancer - Alimov N (Academia One, 2023)
Renal cell carcinoma, a disease arising from malignant epithelial cells in the kidneys. Renal cell carcinoma is responsible for about 90 percent of kidney cancers in adults.
Keywords: carcinoma; renal; kidney